Retelling Legend of City of Kitezh in Video Texts by YouTube Bloggers - M. G. Matlin (Научный диалог)
This article examines the functioning of the traditional genre of Russian folklore, specifically the religious legend, through the example of retelling the legend of the city of Kitezh on YouTube. The paper highlights the specifics of video content on YouTube, which can be defined as multimodal texts. The legend is presented in two main types: variants of texts recorded earlier and texts conveying personal verbalized mystical experience of communication with the city of Kitezh (folklore legend). The paper identifies three main types of retelling the previously recorded variants of the legend: brief retellings, expanded retellings with reference to “The Kitezh Chronicler,” and expanded retellings with the addition of other historical, quasi-historical, and mythological elements. The article establishes that these multimodal texts can be distributed into three groups depending on the number of resources used: weak multimodality — using only two resources; medium multimodality — using three or more resources; strong multimodality — using more than 4—5 resources. The article shows that the told / retold legend is a fragment of a more complex multimodal text or cycle of texts.